Analysis of the Value of Information and Coordination in a Dyadic Closed Loop Supply Chain - Ternero-Saavedra, R; Sepulveda-Rojas, J (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Purpose: This article analyzes the value of information and coordination in a closed loop supply chain (CLSC) and discusses the benefits of a global or local optimization approach and the impact of uncertainty. Methodology: A theoretical dyadic closed loop supply chain is analyzed where the manufacturer re-manufactures products returned by customers, producing “as good as new products” for the retailer. Twelve coordination scenarios were analyzed. For the definition of these scenarios, a framework based on two criteria was proposed: value of information and perimeter of decision making. Findings: Information on returns leads to lower costs than information on demand. In the presence of complete or partial coordination between the actors in the supply chain, it is preferable to have low product return rates. However, if we are in the complete absence of coordination, high rates of return are more convenient as they function as a buffer against uncertainties. The perimeter of decision making (global or local optimization) does not significantly improve the supply chain performance in relation to its costs. Only the exchange of information improves its performance. Therefore, companies should make efforts to exchange information, first, on their lot sizes, then on their returns and finally, on the customer demand. Originality: The novelty of our work relies on an analysis of the closed loop supply chain performance with the simultaneous presence of information, coordination, and uncertainty. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.